Genomics of adipose tissue - Pinnick, K; Karpe, F (S. Karger AG, 2014)
Obesity strongly predisposes to the development of type 2 diabetes (T2D) as well as a myriad of metabolic complications including insulin resistance, ectopic fat deposition, dyslipidaemia, hypertension and cardiovascular disease. During the transition from the lean to obese state, adipose tissue commonly develops dysfunctional features including an impaired capacity to sequester lipids, chronic inflammation and dysregulated adipokine secretion. This deviation from normal function is considered an important component in the aetiology of insulin resistance and T2D. However, not all adipose tissue depots confer equal metabolic risk. Whereas central obesity (visceral and abdominal) is closely associated with the development of metabolic disease, lower-body obesity (thighs and buttocks) has less deleterious effects on metabolic health. Since overall adiposity and body fat distribution both display a strong genetic component, current research aims to understand the genetic and molecular mechanisms which contribute to obesity susceptibility and the pathogenesis of T2DM. Identifying molecular mechanisms which regulate adipose tissue development, function and distribution will aid in the development of novel therapeutic agents for the treatment of metabolic disorders arising as a consequence of adipose tissue dysfunction.